Enhancement of fresh and hardened properties of geopolymeric composite containing toxic lead sludge: A comparative study between the effect of superplasticizer and thermal treatment of sludge. (15th July 2023) - Ramadan, M.; Habib, A.O.; Kohail, Mohamed; Mohsen, Alaa
Abstract: Despite the many environmental and economic advantages resulting from the disposal of sludge containing heavy metals in the fabrication of cementitious materials, using a high quantity of these wastes negatively affects the fresh and hardened properties of developed composites. The previous literature proved that lead sludge (LS) from glass manufacturing elongated the setting time and reduced the workability and compressive strength as it contains a large amount of organic matter that adsorbs a high amount of water and hinders the hydration process. Therefore, the main target of this study is trying to find the best methods to enhance the rheological behavior, setting time and mechanical properties of geopolymeric composites containing 50%slag+50%LS (coded: G) via making a comparative study between the effect of adding two doses from naphthalene-based superplasticizer (0.25 and 0.5 wt% NB-SP, coded G-0.25 and G-0.5, respectively) and replacing the LS with thermally-treated one (LS-500, coded G-500). The results indicated that using LS-500 instead of adding NB-SP greatly impacted the improvement of fresh and hardened properties. It was found that the plastic viscosity values were 0.75, 0.63, 0.49 and 0.36 Pa s, while yield stress values were 47.66, 26.38, 19.97 and 3.99 Pa for G, G-0.25, G-0.5 and G-500, respectively. On the other hand, the composite containing NB-SP with LS delayed the setting time until it exceeded the permissible limits (between 45 and 375 min); therefore, they are not valid for in-situ applications. Meanwhile, the initial/final setting time of the G-500 composite was 233/345 min. At 28-days, G-500 has a compressive strength higher than G, G-0.25 and G-0.5 by 28.6, 66.7 and 104.5%, respectively. These outcomes were matched with the thermal analysis technique (TGA/DTG) as the percentages of binding hydrates (CSHs, CASHs and CAHs) for G, G-0.5 and G-500 were 4.85, 2.54 and 7.61%, respectively. Moreover, the alkali-activation of the G-500 composite created a zeolitic-like phase as well as Pb3 SiO5, which was detected via XRD and SEM techniques. According to the immobilization test (TCLP), the Pb-concentrations in the leachate solutions of G-0.5 and G-500 composites were 11.5 and 2 ppm, respectively. Therefore, it is recommended to use thermal-treated sludge instead of superplasticizers to produce high-performance and safe building materials. Highlights: The organic content in lead sludge has a detrimental impact on the properties of geopolymer. Treated lead sludge enhanced the fresh properties of the generated geopolymeric composites. The inclusion of 50% treated sludge positively affected the mechanical characteristics of alkali-activated composites. The addition of 0.5% superplasticizer impeded the immobilization of lead within the geopolymeric structure.